Marantodes pumilum: Systematic computational approach to identify their therapeutic potential and effectiveness. (30th January 2022) - Azfaralariff, Ahmad; Farahfaiqah, Fazial; Shahid, Muhamad; Sanusi, Siti Aisyah; Law, Douglas; Mohd Isa, Abdul Razak; Muhamad, Mustadza; Tsui, Tee Thiam; Fazry, Shazrul
Abstract: Ethnopharmacological relevance: Marantodes pumilum (MP) herbs, locally known as Kacip Fatimah, are widely used traditionally to improve women's health. The herb is frequently used for gynecological issues such as menstrual problems, facilitating and quickening delivery, post-partum medication, treats flatulence and dysentery, and. MP extracts are thought to aid in the firming and toning of abdominal muscles, tighten breasts and vaginal muscles, and anti-dysmenorrhea. It also was used for the treatment of gonorrhea and hemorrhoids. As MP product has been produced commercially recently, more in-depth studies should be conducted. The presence of numerous active compounds in MP might provide a synergistic effect and potentially offer other health benefits than those already identified and known. Aim of the study: This study aimed to use a computational target fishing approach to predict the possible therapeutic effect of Marantodes pumilum and evaluated their effectivity. Materials and methods: This study involves a computational approach to identify the potential targets by using target fishing. Several databases were used: PubChem database to obtain the chemical structure of interested compounds; Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) server and the SWISSADME web tool to identify and select the compounds having drug-likeness properties; PharmMapper was used to identify top ten target protein of the selected compounds and Online Mendelian Inheritance in Man (OMIM) was used to predict human genetic problems; the gene id of top-10 proteins was obtained from UniProtKB to be analyzed by using GeneMANIA server to check the genes' function and their co-expression; Gene Pathway established by Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) of the selected targets were analyzed by using EnrichR server and confirmed by using DAVID (The Database for Annotation, Visualization and Integrated Discovery) version 6.8 and STRING database. All the interaction data was analyzed by Cytoscape version 3.7.2 software. The protein structure of most putative proteins was obtained from the RCSB protein data bank. Thedocking analysis was conducted using PyRx biological software v0.8 and illustrated by BIOVIA Discovery Studio Visualizer version 20.1.0. As a preliminary evaluation, a cell viability assay using Sulforhodamine B was conducted to evaluate the potential of the predicted therapeutic effect. Results: It was found that four studied compounds are highly correlated with three proteins: EFGR, CDK2, and ESR1. These proteins are highly associated with cancer pathways, especially breast cancer and prostate cancer. Qualitatively, cell proliferation assay conducted shown that the extract has IC50 of 88.69 μg/ml against MCF-7 and 66.51 μg/ml against MDA-MB-231. Conclusions: Natural herbs are one of the most common forms of complementary and alternative medicine, and they play an important role in disease treatment. The results of this study show that in addition to being used traditionally to maintain women's health, the use of Marantodes pumilum indirectly has the potential to protect against the development of cancer cells, especially breast cancer. Therefore, further research is necessary to confirm the potential of this plant to be used in the development of anti-cancer drugs, especially for breast cancer. Graphical abstract: Image 1 Highlights: Systematic computational approach to identify therapeutic potential of Marantodes pumilum . There are 4 potential compounds presents in Marantodes pumil u m which were: apigenin; gallic acid; kaempferol; and pyrogallol. Selected 4 compounds were highly associated with pathway in cancer (breast and prostate) and mammary gland development. Crude extract of Marantodes pumilum successfully inhibit breast cancer growth in-vitro.